CONTESTATION IN PUBLIC SPACES: LEGITIMACY IN EDUCATION IN MATARAM CITY - Akhmad Asyari; Muslehuddin, Muslehuddin (Universitas Islam Negeri Mataram, 2022)
The transformation of the movement in the new order period resulted the diverse variants and contestations in various lines of national and state life. These entities take on different roles in the several scopes such as political, social, cultural organizations and many other focuses in the field of education. This research uses a qualitative research approach carried out in Mataram City, Indonesia. The results of the study illustrate that Mataram City as a cultural locomotive with cultural, ethnic and tribal variations that is able to practice religious rituals and ideologies assisted by various elements of fertility dimension including the existence of various mass organizations such as Nahdlatul Ulama, Muhammadiyah and Salafi which exist in Mataram City. The growing form of religious ideology is encompassed in the family of ahlussunnah waljamaah, between non-sunni subordinates and the same religious Minhaj. The formulation of contestation competes for the space of identity and the pluralization of sunni. In practice, the form of contestation is carried out by strengthening the community of Educational Institutions, prominence of symbols, mass media, as well as spreading the halaqoh and recitation.